2012
DOI: 10.1063/1.4759330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical contact stress on magnetic properties of ferromagnetic film

Abstract: Mechanical and magnetic degradation of ferromagnetic films under contact stress was systematically investigated through novel experiments and analytical simulations. Permalloy (Ni80Fe20) film was deposited onto silicon substrate, and two different thicknesses of permalloy film (50 nm for sample A and 300 nm for sample B) were examined in this study. Magnetic properties were obtained from B-H loop tracer hysteresis measurement, while the mechanical properties (i.e., hardness and elastic modulus) were measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Since this scratching velocity was very low, the frictional heat effect could be neglected. [3][4][5] Also, the applied normal load for scratching the PMR samples ranged from 80 to 600 lN. The stress induced by the applied normal load during the nanoscratch experiments is comparable with that induced by slider-disk contacts.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Since this scratching velocity was very low, the frictional heat effect could be neglected. [3][4][5] Also, the applied normal load for scratching the PMR samples ranged from 80 to 600 lN. The stress induced by the applied normal load during the nanoscratch experiments is comparable with that induced by slider-disk contacts.…”
Section: Methodsmentioning
confidence: 81%
“…Furukawa et al 3,4 revealed that the scratch-induced demagnetization in PMR disks was mainly caused by plastic deformation, which results in magnetic grain tilt. Moreover, Lee et al 5 investigated the plastic yield and magnetic degradation of ferromagnetic films under contact stress by the means of nanoscratch experiments and analytical simulations. Their results showed that the magnetic degradation was more susceptible to the applied contact stress than the plastic yield.…”
Section: Introductionmentioning
confidence: 99%
“…To get more physical understanding on the difference of the nanoscratch depth with the burnishing level, the in situ contact stress during the nanoscratch test was estimated using the Hamilton's sliding contact model [30,31]. Table 1 shows the material properties of the scratch tip and the head slider that were used in the numerical simulation.…”
Section: Nanoscratch Experimentsmentioning
confidence: 99%
“…Wang et al prepared electron irradiated monolithic carbon film by electron cyclotron resonance (ECR) sputtering technique, which has been proved to have relatively high conductivity [4] and paramagnetism [5]. However, it was also found that this kind of film had the limitations of relatively low wear resistance, hardness and poor bonding strength with substrate, which means that it would suffer a higher risk in deformation, spalling and abrasion when facing a contact or friction in MEMS, leading to a change in conductive property [6] or magnetic degradation [7]. In order to improve the tribological and mechanical properties of the electron irradiated film, we constructed a three-layer sandwich structured carbon film by using multilayer coating technique and assembling the electron irradiated film with relatively hard ion irradiated carbon film together.…”
Section: Introductionmentioning
confidence: 97%